Understanding the Christian Association of Nigeria’s Political Activism in the Light of Matthew 5:14 - Ottuh, Peter O. O.; Oghenevwede, Tom (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
Some scholars claim that Nigerian Christians would rather not get involved in politics, but the reality remains that Jesus Christ did not dissuade believers from participating in politics. Other arguments against Christians’ involvement in politics are unpersuasive because many Christians still get involved in politics and have earned positions as governors, senators, and other elected officials in Nigeria. The article looked at the Christian Association of Nigeria (CAN) from a political standpoint and evaluated the biblical foundations of its national politics activism. Matthew 5:14 “You are the light of the world. A city built on a hill cannot be hidden” is used as a metaphor and motivator for CAN’s national political engagement. The paper used historical and evaluative methodologies to attain its aims as a theoretical study. It posited that the Christian Association of Nigeria should define what politics is in the Christian sense, its means of operation, and its political vision for Nigeria as the “light” of Christ.